Development of solar battery indicator - Ahmad Fadzli, Ahmad Tarmugi (2009)
The objective of this project is to create or design the solar battery indicator to monitor the percentage capacity of the battery. The purpose of the use solar energy in this project is to replace the existing energy by use the solar energy to charge the battery using the charging circuit and to improve the solar energy to a new application. This project design is separated into two basic parts which are the charging circuit which is solar charging circuit and the solar battery indicator circuit. The main task of charging circuit use in this project is to charge and store the sun energy from solar panel into the battery. The battery use in this project is 12V 7A lead-acid battery which is fit for storing the energy from the solar panel. The solar battery indicator circuit using as the load for the 12V 7A lead-acid battery. Main task of this circuit is to check the capacity of the battery when the battery is charging and when the battery is use. The circuit will display the percentage of the voltage capacity in the battery by using the seven-segment display and the range of the voltage charge and discharge will use LED as monitoring display.